Impact of Amorphous SiO2 Nanoparticles on a Living Organism: Morphological, Behavioral, and Molecular Biology Implications - Ambrosone, Alfredo; Scotto di Vettimo, Maria Rosaria; Malvindi, Maria Ada; Roopin, Modi; Levy, Oren; Marchesano, Valentina; Pompa, Pier Paolo; Tortiglione, Claudia; Tino, Angela (Frontiers in Bioengineering and Biotechnology, 2014)
It is generally accepted that silica (SiO2) is not toxic. But the increasing use of silica nanoparticles (SiO2NPs) in many different industrial fields has prompted the careful investigation of its toxicity in biological systems. In this report, we describe the effects elicited by SiO2NPs on animal and cell physiology. Stable and monodisperse amorphous silica nanoparticles 25nm in diameter, were administered to living Hydra vulgaris (Cnidaria). The dose-related effects were defined by morphological and behavioural assays. The results revealed an all-or-nothing lethal toxicity with a rather high threshold (35nM NPs) and a LT50 of 38h. At sub lethal doses the morpho-physiological effects included: animal morphology alterations, paralysis of the gastric region, disorganization and depletion of tentacle specialized cells, increase of apoptotic and collapsed cells and reduction of the epithelial cell proliferation rate. Transcriptome analysis (RNAseq) revealed 45 differentially expressed genes, mostly involved in stress response and cuticle renovation. Our results show that Hydra reacts to SiO2NPs, is able to rebalance the animal homeostasis up to a relatively high doses of SiO2NPs and that the physiological modifications are transduced to gene expression modulation.